Recipe books collection - Dawson, Catherine Taylor; Hellier, Mary.
Manuscript recipe books of Catherine Taylor Dawson and Mary Hellier. Also includes other volumes of cookery and home remedy recipes.
Collection material in English.
Keywords: Cooking; Formulas, recipes, etc